Complicated Mechanisms of Class II Transactivator Transcription Deficiency in Small Cell Lung Cancer and Neuroblastoma - Yazawa, Takuya (American Society for Investigative Pathology, 2002)
Small cell lung cancer (SCLC) and neuroblastoma (NB), the most aggressive adult and infant neuroendocrine cancers, respectively, are immunologically characterized by a severe reduction in major histocompatibility complex (MHC) that is indispensable for anti-tumor immunity. We had reported that the severe reduction of MHC in SCLC was caused by a deficient interferon (IFN)-γ-inducible expression of class II transactivator (CIITA) that is known as a very important transcription factor for IFN-γ-inducible class II and class I MHC expression (Yazawa T, Kamma H, Fujiwara M, Matsui M, Horiguchi H, Satoh H, Fujimoto M, Yokohama K, Ogata T: Lack of class II transactivator causes severe deficiency of HLA-DR expression in small cell lung cancer. J Pathol 1999, 187:191–199). Here, we demonstrate that the reduction of MHC in NB was also caused by a deficient IFN-γ-inducible expression of CIITA and that the deficiency in SCLC and NB was caused by similar mechanisms. Human achaete-scute complex homologue (HASH)-1, L-myc, and N-myc, which are specifically overexpressed in SCLC and NB, bound to the E-box in CIITA promoter IV and reduced the transcriptional activity. Anti-sense oligonucleotide experiments revealed that overexpressed L-myc and N-myc lie upstream in the regulatory pathway of HASH-1 expression. The expression of HASH-1 was also up-regulated by IFN-γ. Our results suggest that SCLC and NB have complicated mechanisms of IFN-γ-inducible CIITA transcription deficiency through the overexpressed HASH-1, L-myc, and N-myc. These complicated mechanisms may play an important role in the escape from anti-tumor immunity.